Studying the Relationship among Character, Phantasm and Environment with Customers’ Loyalty in Iran’s Hotel Industry (Case Study: Hotels of Ardabil) - Mehrmanesh, Hassan; Mirmahalleh, Seyed Rahim Safavi (International Review of Management and Marketing, 2017)
Customer loyalty is both an attitudinal and behavioral tendency to favor one brand over all others, whether due to satisfaction with the product or service, its convenience or performance, or simply familiarity and comfort with the brand. Competition in service firms is more than manufacturing firms. Loyalty of the hotel’s guest is of great importance due to the competitive nature of hotel section. Increasing growth of hotels has increased the importance of guests’ loyalty and requires a renewed reservation of the guests in a favorable hotel. Statistical society of this research is the hotels of Ardebil, in the first step sampling is done in cluster form and in the second step sampling is done randomly and clients are available to the selected hotels. The method of this research is descriptive- correlation and the results show that there is a relation among character, phantasm, environment and clients’ loyalty in hotel industry. Keywords: character, phantasm, environment, client’s loyalty, hotel, Ardabil JEL Classifications: C53, C5, E37, E32